2013
DOI: 10.1007/s00268-013-1913-0
|View full text |Cite
|
Sign up to set email alerts
|

How Many Contralateral Papillary Thyroid Carcinomas Can Be Missed?

Abstract: Bilaterality is found more frequently when the tumor is large. Multifocality also can help predict the possibility of bilaterality. Therefore, total thyroidectomy may be necessary for patients with a multifocal or large tumor. It should be noted that the presence of a contralateral cancer is missed in 4.7 and 5.5 % of patients with preoperatively diagnosed unilateral PTC and PTMC, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 22 publications
(26 reference statements)
4
33
2
5
Order By: Relevance
“…[1,2,812] This rate varies across reports, which may be due to population differences and small sample sizes. In the analysis of consecutive cases in our institute from 1999 to 2008, multifocal PTC was observed in 28.6% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2,812] This rate varies across reports, which may be due to population differences and small sample sizes. In the analysis of consecutive cases in our institute from 1999 to 2008, multifocal PTC was observed in 28.6% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] Studies have shown that unilateral multifocality of the primary tumor and the presence of a coexistent benign nodule in the contralateral lobe by preoperative evaluation were independent predictive factors for occult contralateral PTC. [8,9,11,12] Wu et al [11] performed total thyroidectomy in 347 patients with unilateral papillary microcarcinoma combined with coexistent nodules in the contralateral lobe, and occult contralateral PTC was observed in 28.9%. Multivariate analysis showed that unilateral multifocality, presence of coexistent benign nodules in the contralateral lobe, and maximum tumor diameter greater than 5 mm were independent predictive factors of contralateral occult carcinoma, total thyroidectomy was thus suggested for patients with unilateral papillary microcarcinoma if they had any of the following factors: maximum tumor diameter greater than 5 mm, unilateral multifocality, or the presence of coexistent nodules in the contralateral lobe.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted here that no cut-off value of tumor size was determined in our study. Lee et al [10] also reported that bilaterality was found more frequently when the tumor was large. In another study, the presence of three or more tumor foci or bilaterality of tumor tended to be present with larger tumors [11].…”
Section: Discussionmentioning
confidence: 93%
“…[39], общая частота билатерального поражения при папиллярном раке составляет 29,8%: у пациентов с размером опухоли ≥1 см 36,8%, у пациентов с микрокарциномами 25,7%. В данном исследовании диагноз билатераль-ного поражения был основан на гистологическом исследовании у 5,5% пациентов.…”
Section: мультифокальные микрокарциномыunclassified
“…По данным различных авторов, мультифокаль-ность обнаруживается в 15-35,6% случаев микрокар-цином и является важным прогностическим факто-ром персистенции [5,6,10,19,[38][39][40]. Учитывая, что при мультифокальности высока вероятность билате-рального поражения (25-27% случаев), при микро-карциномах рекомендуют проведение тотальной ти-реоидэктомии.…”
Section: мультифокальные микрокарциномыunclassified